Pembuatan tortila jagung (Zea mays L) dari substitusi tepung ampas tahu dan tepung jagung dengan penambahan natrium bikarbonat - Muhammad Said Siregar; Lismadayanti Lismadayanti; Desi Ardilla (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
This study aims to determine the effect of the substitution of tofu flour and corn flour by the addition of sodium bicarbonate in a completely randomized design with two replicates. The first factor is the substitution of tofu flour: corn flour (S) are: S1=100:0, S2=25:75, S3=50:50, S4=75:25, and S5=0:100. The second factor is the effect of adding sodium bicarbonate (P), which consists of three levels, namely: P1=0.00 %, P2=0.20 %, and P3=0.30 %. The observed parameters: protein content, water content, fat content, ash content, and organoleptic texture, color, and flavor. The statistical analysis showed that the substitution of tofu flour: with corn flour provides a highly significant effect (P0.05) on the protein content, water content, fat content, ash content, organoleptic color, flavor, and texture. The effect adding sodium bicarbonate provides a highly significant effect (P0.05) on the protein content, moisture content, fat content, ash content, and organoleptic texture and no significant effect on organoleptic taste and color.